Coseismic Traveling Ionospheric Disturbances during the Mw 7.8 Gorkha, Nepal, Earthquake on 25 April 2015 From Ground and Spaceborne Observations. Issue 10 (21st October 2017) - Tulasi Ram, S.; Sunil, P. S.; Ravi Kumar, M.; Su, S.‐Y.; Tsai, L. C.; Liu, C. H.
Abstract: Coseismic traveling ionospheric disturbances (CTIDs) and their propagation characteristics during Mw 7.8 Gorkha earthquake in Nepal on 25 April 2015 have been investigated using a suite of ground‐based GPS receivers and broadband seismometers along with the spaceborne radio occultation observations over the Indian subcontinent region. Depletion in vertical total electron content, a so called ionospheric hole, is observed near the epicenter 9–11 min after the onset of earthquake. A positive pulse preceding the depletion, similar to N‐shaped perturbation, propagating with an apparent velocity of 2.4 km/s is observed on the south. Further, the CTIDs in the southward direction are found to split in to fast ( 2.4–1.7 km/s) and slow ( 680–520 m/s) propagating modes at epicentral distances greater than 800 km. However, the velocities of fast mode CTIDs are significantly smaller than the surface Rayleigh wave velocity ( 3.7 km/s), indicating that they are not the true imprint of Rayleigh wave, instead, can probably be attributed to the superimposed wave front formed by the mixture of acoustic waves excited by main shock and propagating Rayleigh wave. The southward CTIDs are found to propagate at F 2 region altitudes of 300–440 km captured by Constellation Observing System for Meteorology, Ionosphere and Climate radio occultation observations. The CTIDs with periods of 4–6 min are observed in all directions with significantly larger amplitudes and faster propagation velocities in south and east directions. The observed azimuthal asymmetry in the amplitudes and velocities of CTIDs are discussed in terms of the alignment with geomagnetic field and nature of surface crustal deformation during the earthquake. Plain Language Summary: The sudden piston‐like movement of Earth's surface during earthquakes causes air perturbations (acoustic waves) in the atmosphere which can travel to greater heights in the Earth's atmosphere. In this study, the earthquake‐induced acoustic waves were detected at ionospheric altitudes of 300–440 km from the Earth's surface. The waves observed in the upper atmosphere often provide useful information about the nature of Earth's surface breakups and the direction of destruction propagated during the earthquakes. Therefore, tracing of earthquake induced waves in upper atmosphere is a novel tool with many applications in earthquake studies and helpful to predict tsunamis. Key Points: CTIDs are significantly larger in southeast direction due to effect of geomagnetic field and the nature of coseismic surface deformation Southward CTIDs split into fast ( 2.4–1.7 km/s) and slow (680–520 m/s) modes at 800 km, however, much slower than the surface Rayleigh wave Direct evidence for CTIDs propagating at F 2 layer peak altitudes ( 300–440 km) detected from COSMIC radio occultation observations